INVESTIGATION OF ASPHALT PAVEMENT WITH ADDED CRUMB RUBBER (Advances in Civil and Architectural Engineering, 2014)
Waste tires must be recycled in environmentally safe ways that meet civil engineering concerns while fulfilling standards for construction materials. Used tires can be processed into rubber powders with particle sizes of 0–2 mm, a suitable fine aggregate for mixing into road pavements. We tested asphalt mixtures with rubber added using the dry method, comparing their properties with a traditional mixture. We tested asphalt–rubber mixtures with rubber incorporated at either ambient temperature or preheated. Rubberized and traditional asphaltconcretes compared well in void content, indirect tensile strength ratio, rut depth, and wheel-track slope. After optimizing the rubber content added, we laid an experimental road course with the asphalt–rubber mixture.